Evaluation of water-saving rice status based on morphophysiological characteristics and water use efficiency - Didi Darmadi; AHMAD JUNAEDI; DIDY SOPANDIE; SUPIJATNO; ISKANDAR LUBIS; KOKI HOMMA; NURIL HIDAYATI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Darmadi D, Junaedi A, Sopandie D, Supijatno, Lubis I, Homma K, Hidayati N. 2019. Evaluation of water-saving rice status based on morphophysiological characteristics and water use efficiency. Biodiversitas 20: 2815-2823. One strategy to anticipate water shortages in rice production is to use varieties that are efficient in using water and produce high yields. The aim of this study was to measure water consumption, water use efficiency and production performance of several types of rice. The research was conducted during the rainy season from January to April 2018 and the dry season from August to November 2018 in a greenhouse. This study used a completely randomized design. The genetic materials used were 8 varieties consisting of lowland rice (sawah), upland rice (gogo), and land race. The variables analyzed included morphological and physiological characteristics. The results showed that differences in rice types indicated diverse responses to morphological and physiological characteristics on water consumption and water use efficiency (WUE). Mentik Wangi variety had the highest water consumption of 24.1 liters. The IPB 9 G and Jatiluhur varieties achieved the highest water use efficiency of 2.4 and 2.3, respectively. Based on the heatmap analysis, both varieties had similarities in the morphological characteristics of long roots, high root weights, long and broad leaves, and high total grain counts per panicle. The similarity of physiological characteristics was high rates of photosynthesis and low transpiration. Varieties that achieve the highest water use efficiency have the potential to be developed into varieties that are tolerant to limited water conditions.